Maintenance Therapy With Everolimus for Subependymal Giant Cell Astrocytoma in Patients With Tuberous Sclerosis – Final Results From the EMINENTS Study - Bobeff, Katarzyna; Krajewska, Karolina; Baranska, Dobromila; Kotulska, Katarzyna; Jozwiak, Sergiusz; Mlynarski, Wojciech; Trelinska, Joanna (Frontiers in Neurology, 2021)
The aim of this EMINENTS prospective, single-center, open-label, single-arm study was to evaluate the cumulative efficacy and safety of reduced doses of everolimus (maintenance therapy) in patients with tuberous sclerosis and subependymal giant cell astrocytoma (SEGA). Methods: The trial included 15 patients who had undergone at least 12 months of treatment with a standard everolimus dose. The dose of everolimus was reduced to three times a week, with a daily dose as in standard regiment. Data of 14 patients were analyzed. SEGA volume (SV) was evaluated at study entry and subsequent time points by an experienced radiologist. Adverse events (AEs) noted during maintenance therapy were compared to the AEs of standard dose period. Results: Patients were followed over a mean duration 58.37 months (95%CI: 45.95-70.78). The differences in SV between subsequent time points (0, 3, 6,12, 18, 24, 36, 48 and 60 months) were not statistically significant (p=0.16). At the end of the study, 7 out of 10 patients had stable SV. No clinical symptoms of progression were observed in any patients. No patient or tumor-related risk factors of progression were identified. Regarding AEs, infections (stomatitis, bronchitis, diarrhea) and laboratory abnormalities (neutropenia, anemia, hyperglycemia) occurred less frequently during maintenance therapy compared to the standard dose regimen. Conclusions: Final results from EMINENTS study confirm that maintenance therapy with everolimus might represent a rational therapeutic option for patients TSC and SEGA after effective full dose treatment. It could be an option for patients who experienced everolimus-related AEs, instead of discontinuation of therapy. Careful evaluation of possible progression, especially concerning first six months of maintenance therapy should be advised. Clinical Trial: German Clinical Trials Register (DRKS) (ID: DRKS00005584, http://apps.who.int/trialsearch/)